Asas Keseimbangan dalam Perjanjian Penerbitan Letter of Credit Sebagai Transaksi Bisnis Internasional - Lubis, Zaned Zihan Sosa Elsera; Nur, M.; Sanusi, Sanusi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 8 No 2 (2019), 2019)
Letter of Credit is one of the payment instruments in international business transactions. Based on the agreement to issue a Letter of Credit, the Letter of Credit is issued by the issuing bank at the request of the applicant as the importer. The Letter of Credit agreement that is used by banks, in general, is a standard agreement that the clause has been prepared in advance by the bank. The imbalance in the standard agreement can be used by parties whose bargaining position is stronger to abuse the situation. The purpose of this study is to analyze national law and international law related to the issuance of the Letter of Credit. The next objective is to analyze the application of the principle of balance in the agreement to issue the Letter of Credit as an international business transaction. The type of research used is normative legal research using a statutory approach, the sources of legal materials used based on library research are analyzed qualitatively. The results of the study revealed that whether the principle of balance in the Letter of Credit issuance agreement had been realized in the practice of international business transactions. Letter of Credit adalah salah satu instrumen pembayaran dalam transaksi bisnis internasional. Atas dasar perjanjian penerbitan Letter of Credit maka Letter of Credit  diterbitkan oleh bank penerbit atas permintaan pemohon selaku importir. Perjanjian penerbitan Letter of Credit yang dipakai perbankan pada umumnya adalah perjanjian baku yang klausulanya telah disusun sebelumnya oleh bank. Ketidakseimbangan dalam perjanjian baku dapat dimanfaatkan oleh pihak yang bargaining position-nya lebih kuat untuk melakukan penyalahgunaan keadaan. Tujuan penelitian ini adalah untuk menganalisis hukum nasional dan hukum internasional yang terkait dengan penerbitan Letter of Credit. Tujuan selanjutnya adalah untuk menganalisis penerapan asas keseimbangan dalam perjanjian penerbitan Letter of Credit sebagai transaksi bisnis internasional. Jenis penelitian yang digunakan adalah penelitian hukum normatif dengan memakai pendekatan perundang-undangan, sumber bahan hukum yang digunakan berdasarkan penelitian kepustakaan dianalisis secara kualitatif. Hasil penelitian mengungkapkan bahwa apakah asas keseimbangan dalam perjanjian penerbitan Letter of Credit telah terwujud dalam praktik transaksi bisnis internasional.